ANALISIS PENGARUH PEMANFAATAN IT, KECERDASAN INTELEKTUAL,DAN PENGEMBANGAN KOMPETENSI SDM TERHADAP PERBAIKAN KINERJA LAYANAN PADA KANTOR KEMENAG KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN - Idrus, Sri Wahyuni (KINDAI, 2024)
This study aims to determine how much Analysis of the Effect of Utilization of IT, Intellectual Intelligence, and HR Competency Development on Service Performance Improvement at the Ministry of Religion Office of Tabalong Regency, South Kalimantan Province, the method used in this study is a quantitative method, with a population of 63, a sample of 63 people and data analysis techniques in this study using multiple linear regression test. With the calculated value of f, it shows that the value of Fcount (9.015) > Ftable (2.760) and t count the tcount value of IT Utilization (X1) (2.220) > t table (1.671), Intellectual (X2), obtained the t count value (2.189) > t table (1,671) and HR Competency (X3), the value of t count (2,029) > t table (1,671) is obtained Key words : Utilization of It, Intellectual Intelligence, HR Competency Development, Discipline and Service Performance